Honk, Honk! Hold Tight! - Souhami, Jessica (Great Britain Frances Lincoln Children's Books, 2015)
PICTURE STORYBOOKS. This very funny folktale tells about the princess who will not laugh. Her father says he will give her hand in marriage to the man who can make her laugh - and one boy plus a golden goose set off to the palace to try their luck...As they go along, the animals and people they meet all try to steal one of the golden goose's feathers - and they stick fast to the goose. "Honk Honk Hold Tight!" says the boy, and the whole parade soon ends up at the palace. What will the princess do? A fabulous read-aloud, laugh-out-loud story that has its origins in Italy, Germany, Norway, Sweden and the UK, with variants discovered in Russia and Egypt.